Cool‐1‐Mediated Inhibition of c‐Cbl Modulates Multiple Critical Properties of Glioblastomas, Including the Ability to Generate Tumors In Vivo. (May 2014) - Stevens, Brett M.; Folts, Christopher J.; Cui, Wanchang; Bardin, Addie L.; Walter, Kevin; Carson‐Walter, Eleanor; Vescovi, Angelo; Noble, Mark
Abstract We discovered that glioblastoma (GBM) cells use Cool‐1/β‐pix to inhibit normal activation of the c‐Cbl ubiquitin ligase via the redox/Fyn/c‐Cbl pathway and that c‐Cbl inhibition is critical for GBM cell function. Restoring normal c‐Cbl activity by Cool‐1 knockdown in vitro reduced GBM cell division, almost eliminated generation of adhesion‐independent spheroids, reduced the representation of cells expressing antigens thought to identify tumor initiating cells (TICs), reduced levels of several proteins of critical importance in TIC function (such as Notch‐1 and Sox2), and increased sensitivity to BCNU (carmustine) and temozolomide (TMZ). In vivo, Cool‐1 knockdown greatly suppressed the ability of GBM cells to generate tumors, an outcome that was c‐Cbl dependent. In contrast, Cool‐1 knockdown did not reduce division or increase BCNU or TMZ sensitivity in primary glial progenitor cells and Cool‐1/c‐Cbl complexes were not found in normal brain tissue. Our studies provide the first evidence that Cool‐1 may be critical in the biology of human tumors, that suppression of c‐Cbl by Cool‐1 may be critical for generation of at least a subset of GBMs and offer a novel target that appears to be selectively necessary for TIC function and modulates chemoresistance in GBM cells. Targeting such proteins that inhibit c‐Cbl offers potentially attractive opportunities for therapeutic development. Stem Cells2014;32:1124–1135